PENGEMBANGAN LKS BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI PRISMA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA - Nur Izzatun Nisa Liliyan; Toto' Bara Setiawan; Lela Nur Safrida; Erfan Yudianto; Reza Ambarwati; Dhanar Dwi Hary Jatmiko (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2021)
Student worksheet based on Problem Based Learning (PBL) is a learning media that presents questions in the form of contextual problems so as to stimulate students' thinking skills. This type of research is development research using the Thiagarajan model or the Four-D Model which aims to describe the process and results of developing PBL-based student worksheets for class VIII students on Prism material that is valid, practical, and effective in training students' creative thinking skills. The method used in this research is the questionnaire method to determine the validity and practicality of the student worksheets and the test method to determine the effectiveness. The results of this study are the achievement of increasing students' creative thinking skills with very good interpretations. The student worksheets based on PBL model on prism material produced were declared valid, practical, and effective. This student worksheet could be used to improve students' creative thinking skills.